Young Stellar Population of the Cygnus Star-Forming Field - LeMieux, Henri (Proceedings of the Wisconsin Space Conference, 2016)
We provide homogeneous estimates of the color excess and distance to several open clusters located toward the prominent nebulosity Sh 2-109 in Cygnus. We found these clusters to form two layers at distances …. LY from the Sun which has implication on the structure of the Cygnus star-forming field.